Ego Depletion versus Professional Commitment: The Auditor’s Role in Judgment Decision Making and Skepticism - Rahayuningsih, Deasy Ariyanti; Widayati, Nurti; Pujisari, Yusti; Biyanto, Frasto (Reviu Akuntansi, Manajemen, dan Bisnis, 2026)
Purpose: This study examines the effect of ego depletion on professional commitment, with Judgment Decision-Making (JDM) and professional skepticism as mediating variables. Research Methodology: A quantitative explanatory design was employed. Using convenience sampling, data were collected from 113 active external auditors in public accounting firms (Kantor Akuntan Publik/KAP) in Jakarta and parts of Java Island through an online survey. The hypotheses were tested using Partial Least Squares Structural Equation Modeling (PLS-SEM). Results: Ego depletion significantly and negatively affects JDM and professional skepticism. However, its direct effect on professional commitment is not significant. JDM and professional skepticism fully mediate the relationship between ego depletion and professional commitment. Conclusions: Cognitive resource depletion weakens auditors’ judgment quality and professional skepticism, which subsequently undermines professional commitment. The findings support the Strength Model of Self-Regulation by demonstrating that depleted cognitive resources can hinder the manifestation of professional values. Limitations: The cross-sectional design limits causal inference, while self-reported data may involve social desirability bias. The sample is also limited to accounting professionals, restricting generalizability. Contributions: This study extends ego depletion literature by identifying JDM and professional skepticism as full mediators. Practically, audit firms should manage workloads and cognitive overload to protect auditors’ judgment, skepticism, and professional commitment. Future research should use longitudinal or experimental designs and examine the moderating role of character traits such as courage.